Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus Ombudsman Republik Indonesia) - Christopher Yudha Erlangga (Jurnal Komunikasi, 2017)
This study aimed to analyse the Influence of Leadership Style, Employee Motivation and Performance of the Ombudsman of the Republic of Indonesia. The subjects were central office clerk Ombudsman Indonesi numbered as many as 68 respondents. Data was collected using a questionnaire, of 68 questionnaires distributed, 64 returned the questionnaire and which can be evaluated by 64 questionnaire.The tools used in this research is multiple linear regression with SPSS (Statistical Package for Social Science) version 17.0 This study resulted in three discoveries in accordance with the proposed hypothesis. First Leadership Style significant effect on the performance of employees. Both found Motivation significant effect on the performance of employees and Discipline significant effect on the performance of employees. Keywords: Human Resources, Leadership Styles, Motivation, Discipline, Performance